Evaluating free-bound polyphenols, flavonoids and antioxidant properties of pigmented maize landraces - Pallabika Gogoi; Paras Sharma; Giridhar Goudar; Anwesha Mahajan; R. Ananthan; Mohar Singh; Anita Kumari; Subhash Kalpuri; T. Longvah (Food Chemistry Advances)
Pigmented grains are rich sources of bioactive compounds which can act as antioxidants and has potential to scavenge free radicals and singlet oxygen ions. This study aimed to evaluate the polyphenolic profiling of 11 Indian pigmented maize landraces and their in-vitro anti-oxidant potential. HPLC was used to quantify individual polyphenols whilst anti-oxidant activity was measured using ferric reducing antioxidant power, 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity, reducing power, metal chelation and 2,2-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid scavenging activity. The maize landraces had a good amount of phenolics (576 to 1385 mg GAE/100 g), flavonoids (664 to 1518 mg CE/100 g), anthocyanins (1.62 to 5.40 mg C3G/100 g), pro-anthocyanins (44.9 to 83.0 μg CE/g) and exhibited antioxidant capacity. A total of 19 individual polyphenols were analyzed, which were observed in most of the pigmented maize. The white maize depicted comparatively higher phenolics, and all the maize showed higher in-vitro antioxidant properties in the free fraction of phenolic acid. The bound phenolics and flavonoids were primary contributors to the total phenolic (106 to 799 mg GAE/100 g) and flavonoids (317 to 982 mg CE/100 g). Higher levels of ferulic acid and sinapic acid were observed in the bound fractions. This study revealed that pigmented maize shows high free and bound polyphenolic content and antioxidant activity, which may be used for future breeding and enhance germplasm utilization in the field of agriculture.